PENOLAKAN DALAM BAHASA INGGRIS DAN BAHASA INDONESIA - FX Nadar; I Dewa Putu Wijana; Soepomo Poedjosoedarmo; Stephanus Djawanai (Humaniora, 2005)
This paper discusses refusals in English and in Indonesian and is presented within the framework of pragmatics. The goal is to describe and compare the language politeness strategies used in refusals of both languages. Three hundred and ninety refusals in English and 390 refusals in Indonesian were used as data corpus. Both languages employ some strategies found in Brown and Levinson’s compiled language politeness strategies. However, as compared to refusals in Indonesian, more refusals in English are expressed in single speech acts and combination of two speech acts. Fewer refusals are expressed in combination of three and four speech acts. Refusals in English and in Indonesian also have different inclination in the use of speech act types to express refusals.